PENGARUH WORKLOAD, WORK STRESS, DAN WORK ENVIRONMENT TERHADAP TURNOVER INTENTION (STUDI KASUS PADA KARYAWAN TOKO RITEL) - Belzara, Ghea Syahnita; Waluyo, Dwi Eko (JURNAL ILMIAH EDUNOMIKA, 2024)
In the retail industry, employees are considered the backbone of operations because they play a role in running the store's daily operations. However, many retail store employees experience discomfort while working and some of them even have the intention to leave their jobs. To reduce turnover intention, managers or company leaders must pay attention to factors that influence it, such as Workload, Work Stress, and Work Environment. This research seeks to examine The Effect of Workload, Work Stress, and Work Environment on Turnover Intention (Study on employees of Retail Stores). The study employed a quantitative method, utilizing Smart PLS version 4.0. Data was gathered through questionnaires, which were tested for validity and reliability (outer model). Subsequently, the structural model (inner model) was evaluated, which involved calculating the coefficient of determination (RÂ²) and testing the hypotheses. The results indicated that workload and work stress had a significant impact on turnover intention, whereas the work environment did not significantly influence employee turnover intention.